If p/(b-c)(b+c-2a)=q/(c-a)(c+a-2b)=r/(a-b)(a+b-2c) then find the value of p+q+r=?
Answers
Answered by
2
First of all
![\frac{p}{(b - c)(b + c - 2a)} = \frac{q}{(c - a)(c + a - 2b)} = \alpha \frac{p}{(b - c)(b + c - 2a)} = \frac{q}{(c - a)(c + a - 2b)} = \alpha](https://tex.z-dn.net/?f=+%5Cfrac%7Bp%7D%7B%28b+-+c%29%28b+%2B+c+-+2a%29%7D+%3D+%5Cfrac%7Bq%7D%7B%28c+-+a%29%28c+%2B+a+-+2b%29%7D+%3D+%5Calpha+)
![\frac{r}{(a - b)(a + b - 2c)} = \alpha \frac{r}{(a - b)(a + b - 2c)} = \alpha](https://tex.z-dn.net/?f=+%5Cfrac%7Br%7D%7B%28a+-+b%29%28a+%2B+b+-+2c%29%7D+%3D+%5Calpha+)
Then
![p = \alpha (b - c)(b + c - 2a) p = \alpha (b - c)(b + c - 2a)](https://tex.z-dn.net/?f=p+%3D+%5Calpha+%28b+-+c%29%28b+%2B+c+-+2a%29)
![q = \alpha (c - a)(c + a - 2b) q = \alpha (c - a)(c + a - 2b)](https://tex.z-dn.net/?f=q+%3D+%5Calpha+%28c+-+a%29%28c+%2B+a+-+2b%29)
![r = \alpha (a - b)(a + b - 2c) r = \alpha (a - b)(a + b - 2c)](https://tex.z-dn.net/?f=r+%3D+%5Calpha+%28a+-+b%29%28a+%2B+b+-+2c%29)
So on adding p, q, and r
We will get
0
Then
So on adding p, q, and r
We will get
0
Similar questions
History,
9 months ago
Math,
9 months ago
Social Sciences,
9 months ago
Math,
1 year ago
Hindi,
1 year ago
Social Sciences,
1 year ago